Review on Green Technology Implementation Challenges in University Data Centre - Mohd, Rashid; Noraziah, Ahmad (American Scientific Publishers, 2017)
A data centre is a network of computer servers used by an organization to either save, process or distribute large amounts of data. A green data centre is a repository of data where electrical, mechanical, lighting and computer systems are designed for maximum energy efficiency and minimum environmental impact. Due to increase demands of data in the university, data centre not only consume high quantities of energy, but produce carbon dioxide along with other IT inefficiencies. With the dynamic changes in technology and the exponential rise in quantities of data, the need for implementing green data centre have become the need of the hour. Green technology in data centre will not only reduce costs and emissions, but will provide operational benefits as well. However, there are challenges that need to be faced in order to implement green technology in university data centre. This review will explore what is green technology is all about, its challenges that may hampered to the implementation in university Data Centre and solutions that may combat the limits.